Synthesis and structure–activity relationship of 2, 6-disubstituted pyridine derivatives as inhibitors of β-amyloid-42 aggregation. Issue 14 (15th July 2016) - Kroth, Heiko; Sreenivasachary, Nampally; Hamel, Anne; Benderitter, Pascal; Varisco, Yvan; Giriens, Valérie; Paganetti, Paolo; Froestl, Wolfgang; Pfeifer, Andrea; Muhs, Andreas
Graphical abstract: Abstract: It is assumed that amyloid-β aggregation is a crucial event in the pathogenesis of Alzheimer's disease. Novel 2, 6-disubstituted pyridine derivatives were designed to interact with the β-sheet conformation of Aβ via donor–acceptor–donor hydrogen bond formation. A series of pyridine derivatives were synthesized and tested regarding their potential to inhibit the aggregation of Aβ. The 2, 6-diaminopyridine moiety was identified as a key component to inhibit Aβ aggregation. Overall, compounds having three 2, 6-disubstituted pyridine units separated by at least one C2- or C3-linker displayed the most potent inhibition of Aβ aggregation.